2015
DOI: 10.1017/s0959270915000064
|View full text |Cite
|
Sign up to set email alerts
|

Population constraints on the Grenada Dove Leptotila wellsi: preliminary findings and proposals from south-west Grenada

Abstract: SummaryThe Critically Endangered Grenada Dove Leptotila wellsi has a very small total population size (< 190 individuals) and faces multiple threats. Over eight weeks in 2012 at the Mount Hartman Estate, we investigated the dove’s habitat selection, established a mongoose index of occupancy and recorded dove use of water sources to help determine key research and conservation needs. Of 12 habitat variables measured, greater levels of canopy cover were the best predictor of dove presence. Tracking tunnels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…All other traits exhibited low phylogenetic signal strength, which is not uncommon in traits such as these that often evolve as a response to differing environmental conditions (Kamilar andCooper 2013, Martin et al 2018). Although our model validation has suggested that many of our predicted values are accurate, these results have to be used cautiously, and would benefit from validation from field data (Ando 2019, Bolton et al 2016.…”
Section: Speciesmentioning
confidence: 99%
“…All other traits exhibited low phylogenetic signal strength, which is not uncommon in traits such as these that often evolve as a response to differing environmental conditions (Kamilar andCooper 2013, Martin et al 2018). Although our model validation has suggested that many of our predicted values are accurate, these results have to be used cautiously, and would benefit from validation from field data (Ando 2019, Bolton et al 2016.…”
Section: Speciesmentioning
confidence: 99%
“…Habitat loss and degradation means that this species exists in small fragmented populations (Rosenberg and Korsmo 2001;Rusk 2008;Rivera-Milán et al 2015). It is threatened by predation from a number of mammalian species as well as habitat destruction from natural damaging events such as hurricanes (Bolton et al 2016). Low encounter rates and cryptic behaviour make surveying this species particularly difficult, requiring intensive monitoring that may cause disturbance (Rivera-Milán et al 2015;Bolton et al 2016;Rusk 2017).…”
Section: Study Species and Sample Collectionmentioning
confidence: 99%
“…It is threatened by predation from a number of mammalian species as well as habitat destruction from natural damaging events such as hurricanes (Bolton et al 2016). Low encounter rates and cryptic behaviour make surveying this species particularly difficult, requiring intensive monitoring that may cause disturbance (Rivera-Milán et al 2015;Bolton et al 2016;Rusk 2017). Therefore, non-invasive sampling methods are required to obtain samples for genetic analysis with minimal disruption to this endangered species.…”
Section: Study Species and Sample Collectionmentioning
confidence: 99%
“…Its historical distribution was once widespread across dry coastal zones in the North‐East, West and South‐West of Grenada, including off‐shore islands (Baptista et al., 2020; Bond, 1973; Clarke, 1905; Lack & Lack, 1973). However, the Grenada Dove has experienced a severe reduction in population size and range with populations now presumed to be limited to sites in the West (Perseverance, Woodford and Beausejour area) and Southwest (Mount [Mt] Hartman Estate and surrounding area) of the Island which are approximately 1.6 km 2 and 2.23 km 2 respectively (Bolton et al., 2015; Rivera‐Milán et al., 2015; Rusk, 2009, 2017).…”
Section: Introductionmentioning
confidence: 99%